Respiratory symptoms, sleep-disordered breathing and biomarkers in nocturnal gastroesophageal reflux - Emilsson, Össur; Benediktsdóttir, Bryndís; Ólafsson, Ísleifur; Cook, Elizabeth; Júlíusson, Sigurður; Björnsson, Einar; Guðlaugsdóttir, Sunna; Guðmundsdóttir, Anna; Mirgorodskaya, Ekaterina; Ljungström, Evert; Arnardóttir, Erna; Gislason, Thórarinn; et al. (BioMed Central Ltd., 2016)
Abstract Background Nocturnal gastroesophageal reflux (nGER) is associated with respiratory symptoms and sleep-disordered breathing (SDB), but the pathogenesis is unclear. We aimed to investigate the association between nGER and respiratory symptoms, exacerbations of respiratory symptoms, SDB and airway inflammation. Methods Participants in the European Community Respiratory Health Survey III in Iceland with nGER symptoms ( n = 48) and age and gender matched controls ( n = 42) were studied by questionnaires, exhaled breath condensate (EBC), particles in exhaled air (PEx) measurements, and a home polygraphic study. An exacerbation of respiratory symptoms was defined as an episode of markedly worse respiratory symptoms in the previous 12 months. Results Asthma and bronchitis symptoms were more common among nGER subjects than controls (54 % vs 29 %, p = 0.01; and 60 % vs 26 %, p < 0.01, respectively), as were exacerbations of respiratory symptoms (19 % vs 5 %, p = 0.04). Objectively measured snoring was more common among subjects with nGER than controls (snores per hour of sleep, median (IQR): 177 (79–281) vs 67 (32–182), p = 0.004). Pepsin (2.5 ng/ml (0.8–5.8) vs 0.8 ng/ml (0.8–3.6), p = 0.03), substance P (741 pg/ml (626–821) vs 623 pg/ml (562–676), p < 0.001) and 8-isoprostane (3.0 pg/ml (2.7–3.9) vs 2.6 pg/ml (2.2–2.9), p = 0.002) in EBC were higher among nGER subjects than controls. Albumin and surfactant protein A in PEx were lower among nGER subjects. These findings were independent of BMI. Conclusion In a general population sample, nGER is associated with symptoms of asthma and bronchitis, as well as exacerbations of respiratory symptoms. Also, nGER is associated with increased respiratory effort during sleep. Biomarker measurements in EBC, PEx and serum indicate that micro-aspiration and neurogenic inflammation are .